Airway pressure as a predictor of cardiac output reduction in prone position spine surgery: A prospective observational study - Yi-Ping Wang; Ping-Ju Chen; Huei-Lien Yu; Jia-Fang Syu; Chun-Yu Wu; Tsung-Ta Wu (Journal of the Formosan Medical Association, 2025)
Background: The prone position is commonly used in surgical procedures and is known to cause significant hemodynamic changes, particularly a reduction in cardiac output. This study aimed to explore the relationship between intra-abdominal pressure (IAP), airway pressure, and cardiac output during spine surgeries under general anesthesia. Methods: Twenty-five patients undergoing elective spine surgery in the prone position were enrolled in this prospective observational study. Cardiac output was monitored using pulse contour analysis, while IAP was measured by the bladder method and airway pressure was recorded from anesthesia machine. Changes in these parameters were analyzed to predict a ≥25% reduction in cardiac output after transitioning from the supine to prone position. Results: Transitioning to the prone position significantly increased both IAP and airway pressure (p < 0.001), while cardiac output decreased by 13%. No significant correlation was observed between changes in IAP and cardiac output; however, a negative correlation was found between increased airway pressure and reduced cardiac output (r = −0.40, p = 0.049). The area under the receiver operating characteristic curve for airway pressure change predicting significant cardiac output reduction was 0.88 (p < 0.001). Conclusion: Airway pressure is a reliable and noninvasive predictor of significant cardiac output reduction in patients undergoing prone position surgery. Monitoring airway pressure may help identify patients at risk for hemodynamic instability during surgery.